Mathematical Modeling of Glutathione Status in Type 2 Diabetics with Vitamin B12 Deficiency - Karamshetty, Varun; Acharya, Jhankar D.; Ghaskadbi, Saroj; Goel, Pranay (Frontiers in Cell and Developmental Biology, 2016)
Deficiencies in vitamin B12 and glutathione (GSH) are associated with a number of diseases including type 2 diabetes mellitus. We tested newly diag- nosed Indian diabetic patients for correlation between their vitamin B12 and GSH, and found it to be weak. Here we seek to examine the theoretical dependence of GSH on vitamin B12 with a mathematical model of 1-carbon metabolism due to Reed and co-workers. We study the methionine cycle of the Reed-Nijhout model by developing a simple ‘stylized model’ that cap- tures its essential topology and whose kinetics are analytically tractable. The analysis shows – somewhat counter-intuitively – that the flux responsible for the homeostasis of homocysteine is, in fact, peripheral to the methionine cycle. Elevation of homocysteine arises from reduced activity of methionine synthase, a vitamin B12-dependent enzyme, however, this does not increase GSH biosynthesis. The model suggests that the lack of vitamin B12–GSH correlation is explained by suppression of activity in the trans-sulfuration pathway that limits the synthesis of cysteine and GSH from homocysteine. We hypothesize this ‘cysteine-block’ is an essential consequence of vitamin B12 deficiency. It can be clinically relevant to appreciate that these secondary effects of vitamin B12 deficiency could be central to its pathophysiology.